Strontium ranelate promotes increased peri-implant bone formation in ovariectomized rats. (Research, Society and Development, 2020)
This study aimed to evaluate the systemic effect of strontium ranelate (SR) on peri-implant bone tissue. Thirty-six adult rats were divided into three experimental groups: sham (SHAM), ovariectomized (OVX) and ovariectomized rats treated with strontium ranelate (OVX-Sr). Strontium ranelate (625mg/kg) was administered by oral gavage on a daily basis. The implants were installed on the tibiae. The euthanasia occurred 42 and 60 days after the implants were installed, and the biomechanical (reverse torque); PCR-RT; histological; immunohistochemical; confocal microscopy and histometric analysis were performed. Quantitative data was subjected to statistical tests with significance level set at p